NeuroD1 reprograms chromatin and transcription factor landscapes to induce the neuronal program. (29th October 2015) - Pataskar, Abhijeet; Jung, Johannes; Smialowski, Pawel; Noack, Florian; Calegari, Federico; Straub, Tobias; Tiwari, Vijay K
Abstract: Cell fate specification relies on the action of critical transcription factors that become available at distinct stages of embryonic development. One such factor is NeuroD1, which is essential for eliciting the neuronal development program and possesses the ability to reprogram other cell types into neurons. Given this capacity, it is important to understand its targets and the mechanism underlying neuronal specification. Here, we show that NeuroD1 directly binds regulatory elements of neuronal genes that are developmentally silenced by epigenetic mechanisms. This targeting is sufficient to initiate events that confer transcriptional competence, including reprogramming of transcription factor landscape, conversion of heterochromatin to euchromatin, and increased chromatin accessibility, indicating potential pioneer factor ability of NeuroD1. The transcriptional induction of neuronal fate genes is maintained via epigenetic memory despite a transient NeuroD1 induction during neurogenesis. NeuroD1 also induces genes involved in the epithelial‐to‐mesenchymal transition, thereby promoting neuronal migration. Our study not only reveals the NeuroD1‐dependent gene regulatory program driving neurogenesis but also increases our understanding of how cell fate specification during development involves a concerted action of transcription factors and epigenetic mechanisms. Synopsis: Using a genome‐wide approach this study delineates the binding requirements and target sites for NeuroD1, illustrating how this factor drives the formation of a transcriptional and epigenetic program to ensure neuronal differentiation. Genome‐wide assessment of NeuroD1 binding reveals its targeting to regulatory elements of critical neuronal development genes. Following expression, NeuroD1 locates to and binds its target genomic locations in a highly sequence‐specific fashion. Prior to NeuroD1 binding, its target sites are developmentally silenced by epigenetic mechanisms and regulatory factors. NeuroD1 binding initiates events that confer transcriptional competence to neuronal fate genes including conversion of heterochromatin to euchromatin and reprogramming of the transcription factor landscape. The transient action of NeuroD1 during neuronal development is sufficient to induce a neuronal gene expression program that is maintained by epigenetic mechanisms. Abstract : Using a genome‐wide approach this study delineates the binding requirements and target sites for NeuroD1, illustrating how this factor drives the formation of a transcriptional and epigenetic program to ensure neuronal differentiation.